2019
DOI: 10.1002/smll.201901176
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Light Activated Thermosensitive Ion Channel to Remotely Control Transgene System for Thrombolysis Therapy

Abstract: Current antithrombotic therapeutic strategies often suffer from severe post‐thrombotic syndromes (PTS), inconvenient daily subcutaneous injections for a long time and short circulation times accompanied by a dose‐dependent risk of intracranial hemorrhage. Aiming at noninvasive, on‐demand, and sustained antithrombotic therapy, a new thrombolysis approach based on the transgene system has been developed to remotely and precisely control the expression of urokinase plasminogen activator (uPA) by bioengineered cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…[9][10][11] Additionally, light-mediated nanoplatforms were deployed for photothermal and photodynamic thrombus therapy through the generation of hyperthermia and reactive oxygen species; this resulted in accelerated drug release and improved thrombolytic efficacy. [12][13][14] Despite promising results, these strategies are limited by tissue damage caused by physical effects, and they have not been implemented in clinical practice. [15] Therefore, it is worth engineering a distinct design strategy with simplified structures but an efficient delivery of the tPA through an Fast and effective thrombolysis using tissue plasminogen activator (tPA) is limited by the poor delivery efficiency of thrombolytic drugs, which is induced by an interrupted bloodstream and delayed recanalization.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Additionally, light-mediated nanoplatforms were deployed for photothermal and photodynamic thrombus therapy through the generation of hyperthermia and reactive oxygen species; this resulted in accelerated drug release and improved thrombolytic efficacy. [12][13][14] Despite promising results, these strategies are limited by tissue damage caused by physical effects, and they have not been implemented in clinical practice. [15] Therefore, it is worth engineering a distinct design strategy with simplified structures but an efficient delivery of the tPA through an Fast and effective thrombolysis using tissue plasminogen activator (tPA) is limited by the poor delivery efficiency of thrombolytic drugs, which is induced by an interrupted bloodstream and delayed recanalization.…”
Section: Introductionmentioning
confidence: 99%
“…Deep vein thrombosis (DVT) seriously endangers human health, and its morbidity, mortality, and disability rates are still high. At present, thrombolytic therapy is one of the effective methods for the treatment of DVT, and systemic thrombolysis is mainly performed through peripheral veins in the clinic. However, the main drawback of urokinase (UK) is its short cycling half-life (9–12 min), resulting in a relatively weak thrombolytic effect when administered at low doses, while a high dose or overdose will increase the potential risk of death from intracranial hemorrhage . Reasonably, to overcome the above limitations, an appropriate thrombolysis drug carrier is needed to improve the efficiency from both drug combination and physical assistance, so as to achieve the purpose of effective thrombolysis under a limited dose (risk) of the UK.…”
Section: Introductionmentioning
confidence: 99%
“…4−6 However, the main drawback of urokinase (UK) is its short cycling half-life (9−12 min), resulting in a relatively weak thrombolytic effect when administered at low doses, while a high dose or overdose will increase the potential risk of death from intracranial hemorrhage. 7 Reasonably, to overcome the above limitations, an appropriate thrombolysis drug carrier is needed to improve the efficiency from both drug combination and physical assistance, so as to achieve the purpose of effective thrombolysis under a limited dose (risk) of the UK.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been found that the early stages of cancer could be diagnosed by analyzing different imaging (such as computed tomography (CT) and magnetic resonance (MR) imaging) and pathology results. [ 22–26 ] Therefore, the construction of multifunctional nanomaterials could improve the diagnostic rate and therapeutic effect against cancer. [ 27–29 ]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been found that the early stages of cancer could be diagnosed by analyzing different imaging (such as computed tomography (CT) and magnetic resonance (MR) imaging) and pathology results. [22][23][24][25][26] Therefore, the construction of multifunctional nanomaterials could improve the diagnostic rate and therapeutic effect against cancer. [27][28][29] Te nanomaterials have shown promising potentials in photonic hyperthermia of cancer due to the low long-term toxicity, high biocompatibility, and satisfactory therapeutic outcomes.…”
mentioning
confidence: 99%